Lifestyle of people with Diabetes mellitus in Primary Health Care (Research, Society and Development, 2023)
This study aims to disclose the lifestyle profile of people with diabetes, who are assisted in a Family Health Strategy (ESF) unit. This is a quantitative, exploratory, survey-type study. For data collection, a questionnaire called “Fantastic Lifestyle” was used, which had, as a non-probabilistic sample, 59 participants with Type 1 and Type 2 Diabetes Mellitus (DM). negative impact was on alcohol and tobacco, which had the respective averages of 3.88 and 3.31. In relation to the domains that should occur changes in lifestyle are: physical and behavioral activities, these presented an average of 1.14 and 2.05. Thus, DM is a pathology that affects a large part of the world's population. Thus, carriers of this disease must be shown that, with the practice of regular physical activities and a healthy diet, it is possible for them to have a better quality of life